Azimuthal Variation in the Surface Wave Velocity of the Philippine Sea Plate - Víctor Corchete (Journal of Marine Science and Engineering)
A study of the azimuthal variation in the surface wave fundamental-mode phase velocity is performed for the Philippine Sea Plate (PSP). This azimuthal variation has been anisotropically inverted for the PSP to determine the isotropic and anisotropic structure of this plate from 0 to 260 km. This azimuthal variation is due to anisotropy in the upper mantle. The crust is found in an isotropic structure, but the lithosphere and asthenosphere exhibit anisotropic structures. For the lithosphere, the main cause of anisotropy is the alignment of anisotropic crystals approximately parallel to the direction of seafloor spreading, and the fast axis of the seismic velocity is in the direction of ~163° of azimuth. For the asthenosphere, the seismic anisotropy can be derived from the lattice-preferred orientation (LPO) in response to the shear strains induced by mantle flow, and the fast axis of the seismic velocity is also the direction of ~163° of azimuth. This result suggests that a mantle flow pattern may occur in the asthenosphere and seems to be approximately parallel to the direction of seafloor spreading observed for the lithosphere. Finally, the changes in the parameter ξ with depth are studied to estimate the depth of the lithosphere–asthenosphere boundary (LAB), observing a clear change in this parameter at 80 km depth.